Development and Evaluation of Antimicrobial and Flavored Film for Using on Pastry Dough [Desenvolvimento E Avaliação de Filme Antimicrobiano Aromatizado Para Aplicação Em Massa de Pastel] - Junqueira-Conceicao Goncalve, M (2011)
The food industry, trying to meet growing consumer demand, is developing active packaging to provide quality and safety for packed food. This research aimed to develop and evaluate the implementation of active flavored films in contact with pastry dough. The active films were evaluated for in vitro antimicrobial activity against Penicillium sp. The mechanical properties of the films, the sorbic acid migration, sensory and in vivo microbiological analyses were also tested. The active films showed better results for in vitro and in vivo microbiological analyses when compared with the film with the sorbic acid incorporated directly on the pastry dough. The incorporation of sorbic acid and flavor affected the mechanical properties of the active films compared to the control film. The flavor addition provided a larger migration of sorbic acid from the film to the pastry dough. Besides the pastry dough packed in the active films showed better sensory results.